Produção in vitro de embriões bovinos com soro de égua em estro - Figueiró, Giuliano Moraes (2001)
As a pre-experiment, the viability of mare´s serum was tested for IVP of bovine embryos. Nine hundred and eighty three oocytes were divided into two treatments: T1 using mare´s serum (MS) and C, the control group, using OCS (oestrus cow serum) as the protein sources. An average cleavage rate of 70%, blastocysts rate of 13% on D7, 16% on D9 and an hatched rate of 5%, with no detectable difference between T1 and C. The viability of MS on IVP was confirmed. Thereafter, the first experiment (E1) was undertaken. In E1 the oocytes were matured in an incubator with humid atmosphere of 5% CO2 at 39ºC during 22 to 24 hours, using TCM-199 + HEPES + LHb + rFSHh with 10% MS collected on the first day of oestrus (E1-T1), 24-48 hours before ovulation (E1-T2) and 24-48 hours post-ovulation (E1-T3), with OCS in the same medium serving as control (E1-C). Matured oocytes were fertilized in TALP-FERT under the same conditions and cultivated in SOF+ 5% MS as described for E1-T1, E1-T2, E1-T3 or OCS as in E1-C, for eight days under mineral oil. The results included a cleavage rate of 78%, blastocysts rate of 19% in D7, 22% in D9 and an hatched rate of 5%. There was an higher production in E1-T1, E1-T2 and E1-T3 when compared with the control group (C) in D7 (p<0,05). In D9 the results of treatments E1-T1 and E1-T2 were better than those obtained in E1-C. Results of E1-T3 brought no differences from the other treatments. The cell number of hatched blastocysts in D9 was higher in E1-T1 and E1-C when compared with E1-T3. The results obtained in E1-T2 showed no differences from other groups. Pregnancy rates at 60 days after ET were reasonable. In experiment 2 (E2) the effect of adding or not LH/FSH to the maturation medium, using MS was compared with OCS as protein source, used as control, using the same protocol of the other experiments. A cleavage rate of 73%, a blastocyst rate of 27% in D7 and 26% in D9 and an hatched rate of 9% was obtained. The blastocyst rate in D7 was lower in the control group than in the other 3 treatments. There was no difference between treatments and control group in the number of cells of hatched or expanded embryos. It was concluded that MS collected at any stage of oestrus is a viable protein source for the culture medium in IVP of bovine embryos and that the addition of LH/FSH in the culture medium is not necessary when using MS as the protein source.